Envy and Altruism in Children - Kirsten Häger (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2010)
Envy and altruism have been studied extensively in adults. Here, we report data from an experiment studying envious and altruistic behavior in children. We study a sample of German school children aged seven to ten in a natural setting. We run two treatments. One treatment investigates envy, the other one studies altruism. Additionally, we collect data on the children's cognitive and social skills, and on their socio-demographic background. Controlling for these factors, we find that older children are significantly more altruistic. Boys care more about their relative position than girls. Socio-demographic information have limited predictive power in both treatments.
Keywords: C91; C99; 330; artefactual field experiment; children; envy; altruism; Kinder; Neid; Altruismus; Feldforschung; Deutschland